(untitled) (Journal of Pathology of Nepal, 2016)
Sideroblastic anemias are a heterogenous group of disorders that have as a common feature with the presence of ringed sideroblasts in the marrow. We present a case of young female, nursing student who presented with increasing palpitation, fatigue and exertional shortness of breath for the last one year. She had a low hemoglobin and high serum iron. Anemia with iron overload prompted us to do bone marrow study and there were 19% ringed sideroblasts and iron overload fulfilling the diagnosis of sideroblastic anemia. We searched for secondary causes of ringed sideroblast but could not find any culprit. Her cytogenetics report was normal and genetic analysis was not done due to financial reason. Since the diagnosis 3 months back, patient is on pyridoxine, folic acid, deferasirox and still needs regular blood transfusion suggesting that she may be pyridoxine refractory and may develop iron overload.